Na+ absorption by Claudius’ cells is regulated by purinergic signaling in the cochlea - Yoo, Jae Chul; Kim, Hye-Young; Han, Kyu-Hee; Oh, Seung Ha; Chang, Sun O; Marcus, Daniel C.; Lee, Jun Ho (My University, 2012)
Conclusion: Claudius’ cells absorb Na+ through the amiloride-sensitive epithelial sodium channel (ENaC). Transepithelial ion transport through ENaC and possibly a Cl[superscript]- secretory pathway is regulated by P2Y purinergic signaling. Objectives: The purpose of this study was to investigate the ion transport in the Claudius’ cells and its purinergic regulation. Method: Young adult Sprague–Dawley rats and gerbils were studied. The Claudius’ cell layer on the basilar membrane was dissected from the basal turn of the cochlea. The voltage-sensitive vibrating probe was used to measure transepithelial short circuit current (I[subscript]sc). The baseline I[subscript]sc of Claudius’ cells was measured in the perilymph-like control solution and the change of Isc after application of amiloride (10 μM) or uridine triphosphate (UTP, 100 μM). Results: A negative baseline I[subscript]sc was observed in the control solution (-12.50 ± 3.95 μA/cm[superscript]2, n=8) and the addition of amiloride resulted in a decrease of I[subscript]sc by 75.8%. The application of UTP, an agonist for P2Y purinergic receptors, led to a partial inhibition of Isc (by 38.2 ± 3.2%, n=5), and subsequent addition of amiloride abolished the remaining I[subscript]sc.
Keywords: Epithelial sodium channel; Purinergic receptor; Voltage-sensitive vibrating probe; Rat; Gerbil